The diagnostic approach to anaemia in the dog and cat - PALTRINIERI, SAVERIO (Journal of the Hellenic Veterinary Medical Society, 2017)
The term anaemia indicates a pathologic condition characterized by a decreased concentration of hemoglobin (Hb) in blood, usually associated with a decreased number of erythrocytes (RBC) and/or of hematocrit (Ht). Anaemia depends on two pathogenic mechanisms: 1) decreased RBC production due toxic, infectious or idiopathic bone marrow diseases or to metabolic, neoplastic or infectious diseases that secondarily affect erythropoiesis, leading to the so-called “non regenerative anaemia”, on which no reticulocytes are released in blood from bone marrow; 2) decreased lifespan of mature RBC due to acute blood loss or hemolysis that leads to “regenerative anaemia” in which reticulocytes are released in blood as an attempt to restore the RBC mass. A stepwise diagnostic approach to anaemic dogs and cats may allow first to identify which of the two mechanisms is involved in the pathogenesis of anaemia, then to identify the possible cause of decreased RBC production or of decreased RBC lifespan. This approach must include clinical data, information regarding gross appearance of the sample, actual values of RBC counts, Ht and Hb concentration, RBC indexes (MCV, MCH, MCHC, RDW) and the magnitude of the reticulocyte response. Morphology of blood cells and additional laboratory tests may further address the diagnosis. With rare exceptions, non regenerative anaemia is normocytic normochromic, while regenerative anaemia is macrocytic hypochromic and characterized by anisocytosis and polychromasia, since reticulocytes are larger and have less Hb than mature RBC. However, blood loss or hemolytic anaemia are initially “pre-regenerative” (normocytic and normochromic), then they shift to the macrocytic hypochromic pattern in a few days, when reticulocytosis becomes relevant. Microcytic hypochromic anaemia is usually associated with iron deficiency. Once anaemia is classified into one of the categories listed above, morphology of RBC may suggest the possible cause, especially in regenerative anaemia, when the shape of RBC may be consistent with oxidative damage (eccentrocytes, Heinz bodies), immune-mediated mechanisms (agglutination, spherocytes, schistocytes, etc) or infectious diseases (e.g. mycoplasmosis, babesiosis). If needed, bone marrow cytology, Coomb’s test or flow cytometric detection of anti-RBC antibodies, coagulation profiles or additional biochemical or serological tests may be used to finalize the diagnostic approach.